2021
DOI: 10.1097/cu9.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative opioid-free ureteroscopy discharge: A quality initiative pilot protocol

Abstract: Background: Opioids are commonly prescribed after ureteroscopy. With an increasing adoption of ureteroscopy for management of urolithiasis, this subset of patients is at high risk for opioid dependence. We sought to pilot an opioid-free discharge protocol for patients undergoing ureteroscopy for urolithiasis. Materials and methods: A prospective cohort study was performed of all patients undergoing ureteroscopy for urolithiasis and compared them to a historical control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…23 However, the benefits of a non-opioid post-ureteroscopy analgesic approach are evident, as Sobel et al found that patients who did not receive opioids did not have additional unexpected encounters to the emergency room or clinic, nor extra phone calls for pain. 24,25 And this opioid-free strategy is seen to be feasible in nearly 75% of patients. 24 In addition, robotic-assisted laparoscopic approaches or regional anesthetics and peripheral nerve blocks have been used as tools in other endourologic procedures (such as prostastectomies) to reduce intraoperative and postoperative opioid use.…”
Section: Opioids In Endourologymentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, the benefits of a non-opioid post-ureteroscopy analgesic approach are evident, as Sobel et al found that patients who did not receive opioids did not have additional unexpected encounters to the emergency room or clinic, nor extra phone calls for pain. 24,25 And this opioid-free strategy is seen to be feasible in nearly 75% of patients. 24 In addition, robotic-assisted laparoscopic approaches or regional anesthetics and peripheral nerve blocks have been used as tools in other endourologic procedures (such as prostastectomies) to reduce intraoperative and postoperative opioid use.…”
Section: Opioids In Endourologymentioning
confidence: 99%
“…26 These non-opioid approaches paired with patient education and counseling on expectations have further facilitated post-operative pain control. 25…”
Section: Opioids In Endourologymentioning
confidence: 99%
“…10 Opioid-free discharge has been shown to be safe and feasible for a variety of urologic procedures. [11][12][13] However, there is limited knowledge on the safety and feasibility of opioid-free discharge following nephrectomy. The Michigan Urological Surgery Improvement Collaborative (MUSIC) is a statewide quality improvement (QI) collaborative representing 46 diverse practices and over 260 urologists.…”
mentioning
confidence: 99%
“…10,11 Following ureteroscopic procedures, implementation of an opioid-free discharge protocol did not lead to a significant increase in postoperative pain-related phone calls or emergency department (ED) visits. 9…”
mentioning
confidence: 99%